Semi-analytical BER performance of a direct detection soliton transmission system - Abbou, F. M.; Chuah, Hean Teik; Majumder, Satya Prasad; Abid, A. (The Institute of Electronics, Information and Communication Engineers, 2006)
A semi-analytical approach is presented, to evaluate the bit error rate (BER) performance of a 10 Gb/s direct detection soliton transmission link in the presence of group velocity dispersion (GVD), self-phase modulation (SPM), and accumulated amplifiers' spontaneous emission (ASE). The results show that the BER performance is limited by accumulated ASE and inter-symbol interference due to pulse distortion caused by GVD and SPM. It is found that for transmission distance of 3000-km with cascaded EDFAs the receiver sensitivity corresponding to BER of 10(-9) are -25.2dBm, -20.7dBm and -13.2dBm for amplifier gain of 10 dB, 20 dB and 30 dB respectively.